If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-6x-4=-43+4x-15
We move all terms to the left:
6-6x-4-(-43+4x-15)=0
We add all the numbers together, and all the variables
-6x-(4x-58)+6-4=0
We add all the numbers together, and all the variables
-6x-(4x-58)+2=0
We get rid of parentheses
-6x-4x+58+2=0
We add all the numbers together, and all the variables
-10x+60=0
We move all terms containing x to the left, all other terms to the right
-10x=-60
x=-60/-10
x=+6
| ∠A=5x−12∘∠B=2x+24 | | 80-(3x+4)=3(x+9)+x | | (2x+10)+(4x+32)=90 | | 6m=498 | | 4(w+6)=7 | | x*0.2=6 | | 2x=+711 | | -7(-8x)=105 | | 7(8t+1)-10=t-(t+2) | | 7.3+v=8.9 | | 3(b+4)=3(b-2) | | -7(1-7(1-4m)=13(2m-3) | | 7.11÷a=0.3 | | 7-4r=-15 | | f/23=45 | | 35·n=6 | | 8r+5=28r+9 | | 42x+84=462 | | 25.50=15+3x | | 11x+3x+2x=15+2 | | 5(2x+12)=4(x-9) | | -9x(2x-1)+3(6x+5)=10(5x+16)-75 | | 55+4.50x=82 | | 55x+4.50x=82 | | 2x+3x=-1 | | 55x+4.50=82 | | (2x-3)^2=33 | | -4x+6=12x+6 | | 2.4+w/7=-15.1 | | X-8=4x+2-3x | | 3x+11=2x15 | | X-8=4x+2+ |